Pedagogical Innovations as a Part of Educational Policy in Poland – Trends and Prospects - Zdybel , Dorota (International Dialogues on Education Journal, 2015)
The last 20 years in Polish educational policy has been marked by radical but positive change in the social perception of new, innovative ideas in educational practice. This change, however, came along with important misconceptions, including: superficial/or insubstantial understanding of the very concept of “innovation”, “staging” innovations to fulfill bureaucratic demands. The article explores popular barriers and veiled threats in the process of introducing innovative ideas into schools, searching for potential means of overcoming these barriers. How to bridge the gap between the educational sciences and the school practice? How to prevent the decline in the quality in teacher training? What changes in teacher training are necessary to create the culture of enquiry, self-regulated learning, building learning potential of both, teachers and students? Can innovative teacher training be the answer to bureaucracy, politicization and fake reforms in the Polish educational system? These are the main questions addressed in the presentation.